Is Angiostrongylosis a Realistic Threat for Domestic Cats? - Di Cesare, Angela; Morelli, Simone; Colombo, Mariasole; Simonato, Giulia; Veronesi, Fabrizia; Marcer, Federica; Diakou, Anastasia; D'Angelosante, Roberto; Pantchev, Nikola; Psaralexi, Evanthia; Traversa, Donato (Frontiers in Veterinary Science, 2020)
Three species of Angiostrongylus have been found in felids thus far, i.e. Angiostrongylus chabaudi, Angiostrongylus felineus and Angiostrongylus vasorum. Angiostrongylus chabaudi lives in the right heart and pulmonary arteries of the definitive natural host, the European wildcat (Felis silvestris), and non-patent infections have been reported in domestic cats (Felis catus). Angiostrongylus felineus, described in the Puma yaguarondi (Herpailurus yagouaroundi), has never been reported in domestic felids, while recently an A. vasorum non-patent infection was unequivocally described in a F. catus. Nonetheless, epizootiological and clinical relevance of angiostrongylosis in domestic cats are practically unknown. This study investigated whether cases of angiostrongylosis may be missed in cats living in areas endemic for Angiostrongylus spp. and other metastrongyloids. Overall, 100 cats that were either positive (n.50) or negative (n.50) for metastrongyloid larvae at the Baermann’s test, were examined for Angiostrongylus spp. with DNA-based methods and with the serological test Angio Detect for circulating antigen. The PCR analysis confirmed the copromicroscopy results, where 25 cats scored positive for Aelurostrongylus abstrusus, 16 for Troglostrongylus brevior and 9 for both, while no cats were positive for Angiostrongylus-like larvae, including A. chabaudi. None of the 100 sera samples scored positive at the Angio Detect test. These data suggest that currently feline angiostrongylosis is a minor parasitosis for domestic cats. Nevertheless, it cannot be excluded that the epizootiological drivers which have favored the spillover of A. vasorum and T. brevior from wildlife to dogs and cats, could promote the emergence of feline angiostrongylosis, with an unpredictable health impact.